2023
DOI: 10.1590/2175-8239-jbn-2022-0150en
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of pretransplantation malnutrition risk on the clinical outcome and graft survival of kidney transplant patients

Abstract: Background: The prevalence of malnourished patients before transplantation and the influence of malnutrition on graft and patient outcomes remain underestimated, despite being associated with higher postoperative morbidity and mortality. This study aimed to develop an easy nutritional screening tool and evaluate the impact of nutritional status on clinical outcome, graft survival (GS) and mortality risk in kidney transplant patients (KTP). Methods: In this retrospective cohort study including 451 KTP, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Santos et al found that patients who had higher malnutrition risk scores had worse outcomes and allograft survival. Being able to predict short-term outcomes in kidney transplantation is beneficial in anticipating long-term outcomes and minimizing the requirement for re-transplantation [ 34 ]. According to Tutal et al’s research, individuals who have received a renal transplant may experience malnutrition at an early stage due to a decrease in muscle and fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al found that patients who had higher malnutrition risk scores had worse outcomes and allograft survival. Being able to predict short-term outcomes in kidney transplantation is beneficial in anticipating long-term outcomes and minimizing the requirement for re-transplantation [ 34 ]. According to Tutal et al’s research, individuals who have received a renal transplant may experience malnutrition at an early stage due to a decrease in muscle and fat mass.…”
Section: Discussionmentioning
confidence: 99%